Integration of sensors for dam water quality analysis – a prototype - Lina Rose (IWA Publishing, 2021)
Water consumed is stored in several water bodies in and around us, out of which dams accommodate a major portion of water. The quantity and quality monitoring of water in dams is troublesome due to their large surface area and high depths. Although groundwater resources are the primary water source in India, dams plays a vital role in water distribution and storage network. The Central Water Commission in India has identified more than 5,000 dams of which a major portion is persistently consumed by the rural and urban populations for drinking and irrigation. The water quality of these reservoirs is of serious concern as it would not only affect the socio-economic status of the nation but the aquatic systems as well. Water quality control and management are vital for a delivering clean water supply to the general society. Because of their size, collecting, assessing, and managing a vast volume of water quality data are critical. Water quality data are primarily obtained through manual field sampling; however, real-time sensor monitoring is increasingly being used for more efficient data collection. The literature depicts that the methods involving remote sensing and image processing of water quality analysis consume time, and require sample collection at various depths, analysis of collected samples, and manual interpretations. The objective of this study was to propose a novel cost-effective method to monitor water quality devoid of considerable human intervention. Sensor-based online monitoring aids in assessing the sample with limited technology, at various depths of water in the dam to analyze turbidity which gives the major indication of pure water. The quality analysis of the dam water is suitable if the water is assessed at the distribution end before consumption. Hence, to enhance the water management system, other quality parameters like pH, conductivity, temperature are sensed and monitored in the distribution pipeline. An unstable pH can alter the chemical and microbiological aspects of water, resulting in a variation of other water quality parameters. Temperature variations affect the amount of dissolved oxygen in the water bodies and results in unstable quality parameters. The change in dissolved solvents and the ionic concentration alters the electrical conductivity of the water and the increased concentration of salts also results in turbidity. The data from all the sensors are processed by the microcontroller, transmitted, and displayed in a mobile application comprehensible to the layman. HIGHLIGHTS The quantity and quality monitoring of water in dams is troublesome due to their large surface area and high depths.; An effective quality analysis is the demand of the hour and the problem statement is identified in developing a system to check water quality at various depths in a dam.; An efficient pipeline with various sensors which monitor turbidity, pH, and conductivity is developed as a prototype low cost device.;